Estimating Global Catches of Marine Recreational Fisheries - Freire, Kátia Meirelles Felizola; Belhabib, Dyhia; Espedido, Jeniffer C.; Hood, Lincoln; Kleisner, Kristin M.; Lam, Vicky W. L.; Machado, Michel L.; Mendonça, Jocemar Tomasino; Meeuwig, Jessica J.; Moro, Pietro S.; Motta, Fábio S.; Palomares, Maria-Lourdes D.; et al. (Frontiers in Marine Science, 2020)
Commercial fisheries catches by country are documented since 1950 by the Food and Agriculture Organization (FAO). Unfortunately, this does not hold for marine recreational catches, of which only few, if any, estimates are reported to FAO. We reconstructed preliminary estimates of likely marine recreational catches for 1950–2014, based on independent reconstructions for 125 countries. Our estimates of marine recreational catches that are retained and landed increased globally until the early 1980s, stabilized through the 1990s, and began increasing again thereafter, amounting to around 900,000 t⋅year–1 in 2014. Marine recreational catches thus account for slightly less than 1% of total global marine catches. Trends vary regionally, increasing in Asia, South America and Africa, while slightly decreasing in Europe and Oceania, and strongly decreasing in North America. The derived taxonomic composition indicates that recent catches were dominated by Sparidae (12% of total catches), followed by Scombridae (10%), Carangidae (6%), Gadidae (5%), and Sciaenidae (4%). The importance of Elasmobranchii (sharks and rays) in recreational fisheries in some regions is of concern, given the life-history traits of these taxa. Our preliminary catch reconstruction, despite high data uncertainty, should encourage efforts to improve national data reporting of recreational catches.